Personal, Familial and Socio • Economic Charachteristics of adolescents with Rheumatic fever (1993) - Ehteram - Hajihady (Iran University of Medical Sciences, 1998)
This is a descriptive study of personal, familial, and socio - economic characteristics of adolescents with rheumatic fever referred to clinics of Medical Universities in Tehran. For the purpose of this research a questionnaire consisting of three parts including 33 qquestions was completed by 56 adolescents who were referred to the clinics due to rheumatic fever. The findings were presented in thirty - two tables and further values such as mean and standard deviations were employed. The result indicated that the majority of subjects was male, between 6 - 19 years of age, student suffering repeated sore throat and using antibiotics inconsistantly. They lived in crowded families and parents were either illiterate or had only primary education. The income status of the family was low and had general poor nutrition. Based on the results from nursing services , recomendation for further research was made